A New Class of Proton Conductors with Dramatically Enhanced Stability and High Conductivity for Reversible Solid Oxide Cells. Issue 17 (26th January 2023) - Luo, Zheyu; Zhou, Yucun; Hu, Xueyu; Wang, Weining; Ding, Yong; Zhang, Weilin; Li, Tongtong; Kane, Nicholas; Liu, Zhijun; Liu, Meilin
Abstract: Reversible solid oxide cells based on proton conductors (P‐ReSOCs) have potential to be the most efficient and low‐cost option for large‐scale energy storage and power generation, holding promise as an enabler for the implementation of intermittent renewable energy technologies and the widespread utilization of hydrogen. Here, the rational design of a new class of hexavalent Mo/W‐doped proton‐conducting electrolytes with excellent durability while maintaining high conductivity is reported. Specifically, BaMo(W)0.03 Ce0.71 Yb0.26 O3‐δ exhibits dramatically enhanced chemical stability against high concentrations of steam and carbon dioxide than the state‐of‐the‐art electrolyte materials while retaining similar ionic conductivity. In addition, P‐ReSOCs based on BaW0.03 Ce0.71 Yb0.26 O3‐δ demonstrate high peak power densities of 1.54, 1.03, 0.72, and 0.48 W cm −2 at 650, 600, 550, and 500 °C, respectively, in the fuel cell mode. During steam electrolysis, a high current density of 2.28 A cm −2 is achieved at a cell voltage of 1.3 V at 600 °C, and the electrolysis cell can operate stably with no noticeable degradation when exposed to high humidity of 30% H2 O at −0.5 A cm −2 and 600 °C for over 300 h. Overall, this work demonstrates the promise of donor doping for obtaining proton conductors with both high conductivity and chemical stability for P‐ReSOCs. Abstract : Donor (Mo/W)‐ and acceptor (Yb)‐codoped electrolytes are developed for proton‐conducting reversible solid oxide cells, demonstrating substantially enhanced durability against CO2 and H2 O than the state‐of‐the‐art electrolytes with similar ionic conductivity. The high performance of the new electrolytes is attributed to the careful defect chemistry engineering. In the meantime, donor dopants are responsible for improving chemical stability.